Euro Area and U.S. External Adjustment: The Role of Commodity Prices and Emerging Market Shocks - Massimo Giovannini; Robert Kollmann; Marco Ratto; Werner Roeger; Lukas Vogel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
The trade balances of the Euro Area (EA) and of the US have improved markedly after the Global Financial Crisis. This paper quantifies the drivers of EA and US economic fluctuations and external adjustment, using an estimated (1999-2017) three-region (US, EA, rest of world) DSGE model with trade in manufactured goods and in commodities. In the model, commodity prices reflect global demand and supply conditions. The paper highlights the key contribution of the post-crisis collapse in commodity prices for the EA and US trade balance reversal. Aggregate demand shocks originating in Emerging Markets too had a significant impact on EA and US trade balances. The broader lesson of this paper is that Emerging Markets and commodity shocks are major drivers of advanced countries' trade balances and terms of trade.
Keywords: F2; F3; F4; F2; F3; F4; 330; EA and US external adjustment; commodity markets; emerging markets